Expression of ABA Metabolism-Related Genes Suggests Similarities and Differences Between Seed Dormancy and Bud Dormancy of Peach (Prunus persica) - Wang, Dongling; Gao, Zhenzhen; Du, Peiyong; Xiao, Wei; Tan, Qiuping; Chen, Xiude; Li, Ling; Gao, Dongsheng (Frontiers in Plant Science, 2016)
Dormancy inhibits seed and bud growth of perennial plants until the environmental conditions are optimal for survival. Previous studies indicated that certain co-regulation pathways exist in seed and bud dormancy. In our study, we found that seed and bud dormancy are similar to some extent but show different reactions to chemical treatments that induce breaking of dormancy. Whether the abscisic acid (ABA) regulatory networks are similar in dormant peach seeds and buds is not well known; however, ABA is generally believed to play a critical role in seed and bud dormancy. In peach, some genes putatively involved in ABA synthesis and catabolism were identified and their expression patterns were studied to learn more about ABA homeostasis and the possible crosstalk between bud dormancy and seed dormancy mechanisms. The analysis demonstrated that two 9-cis-epoxycarotenoid dioxygenase-encoding genes seem to be key in regulating ABA biosynthesis to induce seed and bud dormancy. Three CYP707As play an overlapping role in controlling ABA inactivation, resulting in dormancy-release. In addition, Transcript analysis of ABA metabolism-related genes was much similar demonstrated that ABA pathways was similar in the regulation of vegetative and flower bud dormancy, whereas, expression patterns of ABA metabolism-related genes were different in seed dormancy showed that ABA pathway maybe different in regulating seed dormancy in peach.